Optimizing Regional Revenue: The Impact of Taxes, Levies, GRDP, and Population Dynamics in East Java's Regencies - Puri, Salmadella Regita; Restikasari, Wenny (Journal of Regional Economics Indonesia, 2025)
This study investigates the factors influencing regional revenue in East Java's regencies, focusing on the roles of taxes, levies, Gross Regional Domestic Product (GRDP), and population dynamics. Utilizing a quantitative approach, the research analyzes data from various regencies over a specified period, employing multiple regression analysis to assess the relationships between the independent variables and regional revenue. The findings reveal that both taxes and levies significantly contribute to increasing regional revenue, while GRDP demonstrates a positive correlation, indicating that economic growth enhances revenue generation. Additionally, population dynamics are shown to influence regional revenue, with higher population densities leading to increased tax and levy collections. The study underscores the importance of effective tax policies and economic planning in optimizing regional revenue, providing valuable insights for policymakers aiming to enhance fiscal sustainability in East Java. Future research is recommended to explore the impact of additional socio-economic factors on regional revenue generation.